Optimalisasi rumah baca untuk meningkatkan kemampuan literasi masyarakat Pesisir Desa Kwala Gebang - Diyan Yusri; Anjur Perkasa Alam; Muhammad Zahid Albuni Pane; Muhammad Rizki; Ari Anggara (Fusion: Jurnal Pengabdian kepada Masyarakat, 2025)
Reading Houses is a forum for providing reading material for the community in order to meet the needs of the community to access information and knowledge and increase reading hobby. The limitations of facilities and infrastructure in the village make the benefits of reading homes not be felt optimally. This causes a lack of interest and motivation to learn through reading. Even though the development of community literacy is very dependent on reading the people. Kwala Gebang Village is a village located in Gebang District Langkat Regency which has the potential to develop a reading house. Therefore the solution offered is through the community service program, namely the optimization of reading homes to improve the literacy capabilities of the coastal community of Kwala Gebang Village. The program was held from March 15, 2025 to March 22, 2025. The program implementation includes the arrangement of reading houses, the formation of study groups and the implementation of the assistance to read, write and counting. The target of this program is Kindergarten, SD and MTss in Kwala Gebang Village. This program can improve the skills of kindergarten children, elementary and mtss in Kwala Gebang Village. Therefore, the optimization of the reading house is expected to improve literacy capacity, especially the coastal community of Kwala Gebang Village.